Modelling as Semiotic Process - Arianna Ciula; Øyvind Eide; Cristina Marras; Patrick Sahle (Modelling Between Digital and Humanities: Thinking in Practice, 2023)
Chapter 3, Modelling as semiotic process, refers to model-making as theorised within a semiotic framework. This is complementary to but also in contrast with the common theorisation of the practice of modelling in DH informed by the techno-sciences and computer science in particular. Modelling is framed as a process of signification (semiotic process or meaning making). This semiotic framework allows us to see modelling primarily as a strategy to make sense (signification) via practical thinking (creating and manipulating models). It enables to stress the dynamic nature of models and modelling, and to reinstate in renewed terms the understanding of modelling as an open process of signification enacting a triadic cooperation (among object, representamen and interpreter). Referring to Charles Sanders Peirce’s classification of hypoicons, we reflect on some DH examples of modelling in the form of images, diagrams and metaphors, claiming that a semiotic understanding of modelling could ultimately allow us to surpass the rigid duality object vs. model, as well as sign vs. context.